Hakikat Jihad Serta Pemaknaannya dalam Konteks Indonesia - Stevanus, Adolvus; Jagom, Bonifasius; Mahendra, Felix; Wangge, Gregorius Loudowick Lengga; Jie, Marcelino Bramantyoko (Perspektif, 2021)
Jihad is an obligation for all Muslims according to their respective abilities, but jihad has often been misinterpreted as war. The jihad ordered in the Qur’an is not limited to jihad in the meaning of war, but includes many other meanings. Jihad in the Mecca period was carried out not with war, but by devoting all abilities to face the polytheists with sentences that touched reason and heart because they saw the situation and condition of Muslims who were still weak and did not have physical strength. Meanwhile, jihad in the Medina period tended to be interpreted as ‘war’, namely the efforts of the Muslims to retaliate against the attacks aimed at them. In the Indonesian context, jihad is more interpreted as lust jihad, namely fighting the lusts that exist within oneself and also maintaining the noble national values.